Does high body mass index negatively affect the surgical outcome and long-term survival of gastric cancer patients who underwent gastrectomy: A systematic review and meta-analysis. Issue 12 (December 2018) - Zhao, Bochao; Zhang, Jingting; Mei, Di; Luo, Rui; Lu, Huiwen; Xu, Huimian; Huang, Baojun
Abstract: Background: Whether high body mass index (BMI) was associated with increased postoperative complications and unfavorable prognosis of gastric cancer (GC) patients remain controversial. In the present study, we performed a systematic review and meta-analysis to evaluate the impact of high BMI on surgical outcome, postoperative complications and long-term survival of GC patients. Methods: The related studies were identified by searching PubMed and Embase databases. According to the BMI, all GC patients were classified into BMI ≥25 kg/m 2 group and BMI <25 kg/m 2 group. The relevant data was extracted and pooled effect size was assessed using a fixed effect model or random effect model. Results: A total of 36 relevant studies involving 30, 642 GC patients were included in this meta-analysis. The results indicated that high BMI patients had longer operation time, fewer number of retrieved lymph nodes and larger amount of intraoperative blood loss than other patients, regardless of open gastrectomy or laparoscopic gastrectomy. In addition, the risk of postoperative complications was significantly higher in the patients with BMI ≥25 kg/m 2 than in those with BMI <25 kg/m 2, especially for infectious complications. However, high BMI had no negative impact on postoperative mortality and long-term survival of GC patients. Conclusion: Despite the increased surgical difficulty and postoperative complications, high BMI was not associated with the prognosis of GC patients. To reduce the risk of postoperative complications, more meticulous operation technique and improved perioperative management should be necessary for high BMI patients.